Analytical and experimental studies on an innovative steel damper reinforced polyurethane bearing for seismic isolation applications. (15th July 2021) - Yuan, Yong; Wei, Wei; Ni, Zhibo
Highlights: A steel damper reinforced polyurethane bearing (SDRPB) for seismic isolation is developed. The SDRPB combines the advantages of steel damper and polyurethane elastomer. Mechanical behavior and energy dissipation capacity of SDRPB are investigated. An analytical model of SDRPB is proposed and validated by experimental tests. Comparative analysis of a bridge with and without the SDRPB is conducted. Abstract: Isolation bearings are widely applied to mitigate the seismic response of civil structures under strong earthquakes. With the development of material science, various advanced materials have been applied in isolation bearings to meet special demands. In this paper, a steel damper reinforced polyurethane bearing (SDRPB) for protection of structures from earthquake damages is developed by innovative usages of steel damper to reinforce a newly developed polyurethane bearing, simultaneously combining the advantages of hysteretic steel and polyurethane elastomer. This paper first presents a general description and illustration of the SDRPB which is composed of a polyurethane bearing and four specially designed C-shaped steel dampers. Then, mechanical modeling of the SDRPB is derived to fundamentally define its cyclic behavior and obtain essential mechanical parameters, with a particular attention on describing the mechanical behavior of C-shaped steel dampers. Subsequently, a series of quasi-static compression, friction, and cyclic shear tests are conducted to comprehensively investigate the mechanical behavior of SDRPB. The test results show that SDRPB exhibits high strength and energy dissipation capacity, and the accuracy of the proposed mechanical model of SDRPB is examined by comparing the hysteretic loops between the experimental and analytical results. Finally, the SDRPB was applied in a typical multi-span continuous isolated bridge to numerically validate its isolation effects in real engineering scenarios. In conclusion, the SDRPB is expected to be served as a promising option with both large vertical bearing and energy dissipation capacities, making it particularly suitable for seismic isolation applications.